Assessing Consumer Preferences and Intentions to Buy Edamame Produced in the U.S. - Carneiro, Renata C. V.; Drape, Tiffany A.; Neill, Clinton L.; Zhang, Bo; O'Keefe, Sean F.; Duncan, Susan E. (Frontiers in Sustainable Food Systems, 2022)
Due to the growing consumer demand for edamame (vegetable soybean) in the U.S., the domestic production of this specialty crop has been promoted in several Mid-Atlantic and Southeast states as an economically attractive alternative to replace the decreasing tobacco production. For the edamame agrobusiness to be successful in the U.S., consumer studies are as needed as new commercial cultivars that are developed for the U.S. environment. Thus, in this exploratory study, we investigated consumers' preferences and intentions to buy edamame products in the U.S., especially domestic products. Data was collected through a web-based survey distributed through QualtricsXM and a convenience sampling method was chosen. Volunteers who completed the survey (N = 309) were 82% female, 57% residents of the South Atlantic area, and 79% daily consumers of vegetables. Survey respondents had a positive attitude toward domestically produced vegetables and valued supporting U.S. producers. Overall, domestically grown, in-shell edamame products were preferred compared to shelled edamame or imported products. Regarding future purchasing, respondents exhibited higher intention to buy fresh edamame relative to frozen edamame. Additionally, respondents considered price, availability, and familiarity with the vegetable brand, respectively, as the most important factors in their decision-making process to buy edamame products. Our study confirmed there is a market potential for domestically produced edamame and it also provides valuable information to support future studies, production decisions, and the growth of the edamame agrobusiness in the U.S.